Undesirable risks of ozone-resistant bacteria (ORB): biofilm formation potentials and control strategy - Hao-Bin Wang; Yin-Hu Wu; Yuan Bai; Zhuo Chen; Rui-Ning Wang; Han Liu; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Water Research, 2026)

Efficient bioleaching of high-magnesium low-grade copper-nickel sulfide ore: optimization and mechanisms - Duo-Rui Zhang; Dai-Ying Wei; Jing Zhang; Hong-Rui Chen; Zi-Jie Jin; Lei Zheng (Minerals Engineering, 2026)

Integrative multi-omics analysis identifies FAM3D as a prognostic tumor suppressor in cervical cancer - Yanbin Chen; Yu Hong; Dongjun Wei; Lianjiao Fan; Dian Tao; Rui Zhang; Hongwei Yang (Functional & Integrative Genomics, 2026)

Iterative precursor rebalancing improves phenazine-1-carboxylic acid production in engineered Pseudomonas chlororaphis - Sheng-Jie Yue; Peng Huang; Chen Song; Song Li; Rui Lian Yao; Wei Wang; Xue-Hong Zhang; Pablo I. Nikel; Hong-Bo Hu (Bioresource Technology, 2026)

Nitrogen and straw optimization boosts rice growth via arbuscular mycorrhizal fungal communities and soil ecological functions - Rui Chen; Ning Wang; Pei Chen; Yu Cheng; Jian-Guang Yu; Li-Hong Xue; Lin-Zhang Yang (Applied Soil Ecology, 2026)

Catalytic ozonation with N, S co-doped sludge biochar for decontamination: Performance and mechanistic insights - Xinyi Tao; Weiwei Chen; Xuehong Fan; Rui Hu; Xuejian Wang; Shiquan Sun; Yu-Hong Cui; Zheng-Qian Liu (Journal of Environmental Chemical Engineering, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Basalt fabric functionalized with Copper/Silver nanoparticles as a salt-tolerant solar evaporator for all-weather brackish water desalination - Dilibinuer Niyazimaimaiti; Ying-Lin He; Zhuo Chen; Anand Parkash; Jincheng Wu; Ghizlane Achagri; Chun-Hong Zhou; Yuan Fan; Wen-Rui Ma; Peng-Cheng Ma; Abudukeremu Kadier (Journal of Environmental Chemical Engineering, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Calcium-mediated catalytic ozonation for water purification: Synergistic interplay among surface acid-base sites, alkaline interfacial microenvironment and dynamic oxygen supplementation - Hong-Guang Li; Cheng Chen; Zhi-Hang Wu; Ai-Yong Zhang; Rui-Gang Zhang; Shao-Wei Yuan; Ming Du; Jing-Yu Zhang (Water Research, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Water and nutrient mechanism of bioretention systems under plant-filler synergy and seasonal dynamic regulation - Chunbo Jiang; Rui He; Jian Yuan; Hong Chen; Jiake Li (Journal of Environmental Chemical Engineering, 2026)

Catfish MyD88 mediates resistance to Aeromonas hydrophila infection through coordinated IL- and IFN-dependent signaling - Can Yang; Yanfang Wu; Qing Yang; Feiming Chen; Hong Yang; Jinwei Gao; Hao Wu; Zhenzhen Xiong; Jiayu Wu; Dongsheng Ou; Rui Song; Hao Feng (Fish & Shellfish Immunology, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

A crop-growth-coupled simulation-optimization approach for canal system scheduling within water-energy-food nexus - Hui Wu; Chenglong Zhang; Qiong Yue; Rui Chen; Hong Li (Agricultural Systems, 2026)

Zinc and Iron(III) complexes of carboxymethyl Ganoderma polysaccharide: Chelation mechanism, structural features, and in vitro biological activity - Luyu Zhang; Xiaoliang Zhang; Xinyu Qi; Xiaolong Chen; Rui Zhao; Hong Zhuang (Food Bioscience, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Inhibiting hydrolytic enzyme activity and slowing carbohydrate digestion using lotus seed epicarp phenolic extracts - Congcong Wang; Rui Chen; Lingxiao Gong; Hong Xu; Jie Liu; Huijuan Zhang (Natural Product Research, 2026)

New 14,15-dinor- neo -clerodane and neo -clerodane diterpenoids from Ajuga macrosperma Wall. ex benth - Yi-huan Li; Yi-hang Ba; Jian-fen Xiao; Shuai Chen; Tian-qing Zhu; Kai-xiang Liu; Hong-ping He; Hua-yi Jiang; Rui Yang (Natural Product Research, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

The evaluation to combined toxic effects of polypropylene microplastics and benzo[a]pyrene on macrophage cells - Ye-xuan Zhang; Rui Hou; Si-si Chen; Xue-wen Guo; Hong-juan Chen; Li Mao; Wei-juan Zheng; Hong-zhen Lian (Science of The Total Environment, 2026)

The mechanism of reducing the oil content of fried instant noodles by adding sugar alcohol: microstructure, surface properties and molecular structure - Rui He; Xiaomeng Ma; Ju Chen; Chengrong Zheng; Dingwu Zhang; Chong Liu; Jing Hong; Binghua Sun; Mei Liu; Jiaying Shang; Zipeng Liu; Xueling Zheng (Food Research International, 2026)

Inversion of soil heavy metal content in surface coal mine area based on fractional-order derivative and reindeer cyclone optimization algorithm support vector regression - Yuanlin Chen; Hong Wang; Longshan Yang; Yichen Wang; Rui Du (Environmental Geochemistry and Health, 2026)

Erzhi pills: a potential aging-modulating agent targeting immunosenescence in mice - Zhirui Fang; Wei Sun; Na Li; Tingting Shi; Xiuyun Ren; Rui Zhang; Yujing Zhang; Jing Chen; Qi Liu; Meng Wang; Lu Chen; Hong Wang (Biogerontology, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Tracking the eyes to track decline: Global eye movement similarity as a novel neuropsychological marker of mild cognitive impairment - Zhan Wang; Hong-Zhou Xu; Fang Fang; Xue-Rui Peng; Ying-Chen Liu; Zhi-Jun Zhan; Jing Yu (GeroScience, 2026)

Enhancing identification confidence in non-targeted screening of emerging contaminants via an ensemble retention time prediction model: Applications in screening and ecological risk assessment - Ye Liu; Hua-Chun Liu; Tian-Hong Chen; Jian-Ping Deng; Rui-Fang Fan; Hong-Xuan Kuang; Yun-Jiang Yu (Environmental Pollution, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Immunotherapy checkpoint inhibitor-combination therapy versus chemotherapy alone among Chinese population in cholangiocarcinoma treatment: a systematic review and meta-analysis - Li Shi; Wei Du; Juan Miao; Xi-Yuan Peng; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Si-Qi Gao; Hong-Lin Chen (European Journal of Clinical Pharmacology, 2026)

The correlation between social support and hopelessness among cancer survivors: a meta-analysis - Lu-Ting Shen; Jian-Zeng Lan; Attiq-Ur-Rehman; Wei Li; Meng-Wei Ge; Rui Feng; Kang Zhong; Si-qi Gao; Hong-Lin Chen (Cancer Causes & Control, 2026)

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

Time-series InSAR with phase gradient stacking and slope-constrained clustering for large-scale landslide detection in the Sichuan-Tibet Region - Jichao Lv; Rui Zhang; Kun Fang; Kun Chen; Age Shama; Ruikai Hong; Xu He; Guoxiang Liu (Engineering Geology, 2026)

Regional Heatwave Characteristics and Future Projections in China Using NEX ‐ GDDP ‐ CMIP6 Downscaled Data - Rui Zhao; Xilin Xie; Yanling Chen; Hong Wang; Jing Li (International Journal of Climatology, 2025)
Climate change has increased heatwave frequency, duration, and intensity globally, which is expected to worsen under warmer conditions. Understanding heatwave variabilities is crucial for the ecosystem and human health they impact, yet comprehensive assessments over China at different spatiotemporal scales remain limited. This study evaluates 12 NASA Earth Exchange Global Daily Downscaled Projections' CMIP6 (NEX‐GDDP‐CMIP6) downscaled data in simulating historical heatwaves (1981–2010) and their projections under SSP2‐4.5 and SSP5‐8.5 scenarios for near‐term (2031–2060) and late‐term (2071–2100) periods, using CN05.1 observations and key heatwave metrics. The NEX‐GDDP‐CMIP6 ensemble mean (MME) outperforms individual models in simulating heatwave frequency (HWF) and duration (HWD), with 65%–87% of China showing biases within ±10%. While the MME effectively captures HWF trend patterns across China, it fails to simulate decreasing HWD trends over southern China and intensity metrics trends over the Tibetan Plateau. Among the individual models, CMCC‐ESM2, GFDL‐ESM4, and GFDL‐CM4 emerge as the three best‐performing models. Under SSP5‐8.5, about 87% (74%) of regions will experience increases in HWF (HWD). Notably, heatwave frequency over China will exceed 15 events annually during 2071–2100. The entire country will experience intensification of heatwave intensity with larger increments in high‐latitude regions. Furthermore, the likelihood of extreme heatwave events under SSP5‐8.5 is projected to be double under SSP2‐4.5. Northern China faces the highest risk of extreme heatwaves with over 50% probability under late‐term SSP5‐8.5, followed by Southeastern China. Our results offer comprehensive insights into NEX‐GDDP‐CMIP6 simulated heatwave variations, necessary for refining global climate models and understanding future risks.

Improved PSO-VMD seismic signal denoising method combined with modified wavelet transform - Hui Sun; Hong-yong Ren; Rui Chen; Xing-guo Huang; Wei Zhang; Yan-song Li; Jian Zhang; Yu-bo Yue (Applied Geophysics, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Melichumarin A, a new coumarin with nitric oxide inhibitory activity from the stems of Melicope chunii - Rui-Hong Zhu; Zi-Feng Liang; Zhong-Liu Zhou; Zi-Ming Chen; Qi Zhou; Jing-Ling Ren; Shou-Yuan Wu (Natural Product Research, 2025)

Bioactive sulfur-containing amides from the leaves of Glycosmis lucida - Shou-Yuan Wu; Hong-Yan Yang; Zhong-Liu Zhou; Zi-Feng Liang; Rui-Hong Zhu; Jing-Ling Ren; Pei-Lian Liu; Zi-Ming Chen (Natural Product Research, 2025)

Research on Environmental Response Characteristic of Super-Long Inclined Shaft Tunnel and CO Diffusion and Ventilation Optimization of Blasting Procedures - Kong-fei Yu; Huai-bing Wang; Hong-yan Wang; Chen-qi Fan; Bu-rui Liu; Xuan-ke Ren (Applied Geophysics, 2025)

Gas permeability characteristics and pore structure evolution of sandstones with high-temperature damage effects - Jiang-Feng Liu; Hong-Yang Ni; Xu Chen; Shi-Jia Ma; Zhi-Peng Wang; Rui-Nian Sun (International Journal of Rock Mechanics and Mining Sciences, 2025)

The effect of microplastic pollution on rice growth, paddy soil properties, and greenhouse gas emissions: A global meta-analysis - Shi-Wen Deng; Wei Liang; Hong-Yu Chen; Mutaz Mohammed Abdallah; Rui-Long Wang (Environmental Research, 2025)

Extreme Phenotypic Variation Confounds Acanthocephalan Systematics: A Case Study of Longicollum pagrosomi and Pomphorhynchus zhoushanensis (Acanthocephala: Echinorhynchida) - Cui‐Hong Zhao; Hui‐Xia Chen; Matthew Thomas Wayland; Rui‐Jia Yang; Xiao‐Hong Gu; Liang Li (Zoologica Scripta, 2025)
The phylum Acanthocephala is a ubiquitous group of zooparasites, with major socio‐economic importance. The true diversity of the Acanthocephala is obscured by the phenomena of cryptic speciation and a large degree of intraspecific variation. In this study we describe an example of extreme phenotypic variation in neck morphology. The pomphorhynchid acanthocephalans, Longicollum pagrosomi and Pomphorhynchus zhoushanensis were originally differentiated on the basis of differences in neck morphology; P. zhoushanensis possesses a neck bulb whereas this structure is absent in L. pagrosomi . However, ASAP and phylogenetic analyses of the ITS, 12S, cox 1 and cox 2 sequence data, together with comparative mitogenomics, revealed that the two taxa are in fact conspecific. Therefore, the presence or absence of a neck bulb represents extreme phenotypic variation, and this character is not reliable for distinguishing the genera Pomphorhynchus and Longicollum. In the absence of other characters to discriminate the two genera, Longicollum is relegated to a junior synonym of Pomphorhynchus . A new combination Pomphorhynchus pagrosomi (Yamaguti, 1935) comb. nov. is proposed for L. pagrosomi Yamaguti, 1935 and P. zhoushanensis Li, Chen, Amin & Yang, 2017 is relegated to a junior synonym of P. pagrosomi .

Calibration of the Edinburgh Elasto-Plastic Adhesion contact model for modelling clay-moist soil with high moisture content - Xuan Deng; Wencheng Wu; Jiawei You; Rui Jiang; Mengliang Li; Ju Li; Youfeng Tao; Hong Cheng; Wei Zhou; Fei Deng; Yong Chen; Wanjun Ren; et al. (Computers and Electronics in Agriculture, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Synergistic quorum quenching to the diffusible signal factor and AHLs mediated quorum sensing in Thiothrix controlling filamentous sludge bulking - Rui Liu; Lin Feng; Jie Li; Zhuo-Li Yan; Jian-Hong He; Yue Zhi; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Environmental Chemical Engineering, 2025)

Application of Cu5.5Fe1 catalyst from fluidized-bed crystallization reactor for treatment of RB5 azo dye using a Fenton-like system - Rui-Hong Jiang; Thi-Hanh Ha; Chart Chiemchaisri; Wen-Yu Chen; Ming-Chun Lu (Journal of Environmental Chemical Engineering, 2025)

Spatiotemporal evolution and driver analysis of wastewater greenhouse gas emissions in Chinese mainland: Insights and future trends - Yang Chen; Rui Qiu; Min Zheng; Bing-Jie Ni; Hong-Guang Guo (Environmental Research, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Self-healing sodium alginate-PEDOT:PSS conductive hydrogel for accelerated burn wound healing and real-time monitoring - Xinshuo Liu; Feng Chen; Yifan Zhang; Zexiang Zheng; Rui Huang; Jinhuan Tian; Hong Li; Changren Zhou; Shuyun Zhang; Huihua Xu; Lihua Li (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Efficient solar-driven tandem catalysis for biomass valorization: selective C C bond cleavage to synthesize xylitol - Liangdong Hu; Huiyan Zhang; Zupeng Chen; Nengchao Luo; Lian-Hua Xu; Kai Wu; Longfei Hong; Sheng Chu; Rui Xiao (Science Bulletin, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Microplastics Induce Structural Color Deterioration in Fish Poecilia reticulata Mediated by Oxidative Stress - Hong-Yu Ren; Huan-Chao Ma; Rui-Peng He; Cong-Cong Gao; Bin Wen; Jian-Zhong Gao; Zai-Zhong Chen (Fishes, 2025)
Microplastics (MPs) can affect fish health by inducing oxidative stress, but their impact on structural coloration remains poorly understood. This study investigated the effects of environmentally relevant concentrations (16 and 160 μg/L) of MPs and nanoplastics (NPs) exposure on growth, oxidative stress and structural coloration in blue strain guppy fish (Poecilia reticulata). Results showed exposure to 160 μg/L MPs significantly reduced specific growth rate of fish compared to controls. Plastic accumulation followed a dose-dependent pattern, especially within gut concentrations. Oxidative stress responses differed between MPs and NPs: 160 μg/L MPs decreased SOD activity in skin and reduced GSH levels, while 160 μg/L NPs increased MDA levels in gut tissues, indicating severe lipid peroxidation. Structural coloration analysis revealed exposure to 160 μg/L MPs decreased lightness and increased yellowness, demonstrating reduced blue coloration. This was accompanied by an increase in skin uric acid content, suggesting that guanine conversion might occur to combat oxidative stress. These findings demonstrate that MPs, particularly at high concentrations, impair growth and induce oxidative stress in guppies. To counteract stress, guanine in iridophores may be converted into uric acid, leading to a decline in structural coloration. This study is the first to reveal that MPs disrupt structural coloration of fish, providing new insights into the ecological risks of plastic pollution on aquatic organisms.

A state-of-the-art review of underground logistics systems: Research trends, application modes, planning approaches, and future directions - Wanjie Hu; Rui Ren; Jianjun Dong; Xudong Zhao; Wan Hong; Zhilong Chen (Tunnelling and Underground Space Technology, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Multi-target directed ligands design of 1-O-Acetylbritannilactone derivatives: Dual anti-neuroinflammatory and acetylcholinesterase inhibitory activities - Yan-Peng Liang; Qian Gao; Hong Chen; Rui Ma; Xiao-Bo Zhao; Xiao-Jie Jin; Jian Zhang; Yan-Ping Shi; Wei Ha (Phytochemistry Letters, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Micro-nano bubble hydrogen water irrigation improves the Cd tolerance of Ipomoea aquatica Forssk.: Rhizosphere micro-biotas modulation and oxidative stress alleviation - Xin Guo; Rui Chen; Hong Li; Guanlin Li; Qihang Zhao; Duo Wang; Jian Wang (Environmental Pollution, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Effects of Microclimates on Species Richness of Epiphytic and Non‐Epiphytic Bryophytes Along a Subtropical Elevational Gradient in China - Zun Dai; Hong‐Wei Zhang; Hong Qian; Min Li; Rui‐Ping Shi; Zhao‐Chen Zhang; Jian Zhang; Hong‐Qing Li; Jian Wang (Journal of Biogeography, 2025)
Aim Biodiversity patterns along elevational gradients have been well documented for vascular plants and terrestrial vertebrates, but we know relatively little about the elevational patterns of bryophytes and their underlying mechanisms, especially the effect of forest microclimate on epiphytic and non‐epiphytic bryophytes. Here we study the influence of microclimates on the richness of epiphytic and non‐epiphytic bryophytes as a whole, and for liverworts and mosses separately, in forests along an elevational gradient ranging from 369 to 1476 m in a subtropical region. Location Mt. Tianmu in eastern China. Methods We sampled bryophytes in each of 16 vegetation plots, each of the size of 20 by 20 m, along the elevational gradient and distinguished between mosses and liverworts and between epiphytic and non‐epiphytic species. We measured climate conditions at local sites. Species richness of bryophytes along the elevational gradient was related to six microclimate variables, using correlation and regression analyses and a variation partitioning approach. Results Overall, species richness of bryophytes showed a slightly decreasing trend with elevation, and epiphytic and non‐epiphytic bryophyte richness showed different elevational patterns. Compared to non‐epiphytic bryophytes, species richness of epiphytic bryophytes was more influenced by air microclimate. We also found that species richness of bryophytes was influenced by both microclimate extreme variables and microclimate seasonality variables. In sum, utilising in situ air and soil microclimatic monitoring data, our study offers a more accurate assessment of the relationship between bryophyte species richness and their habitats. Main Conclusions Our results highlight the importance of considering the ecological differences between mosses and liverworts, and distinguishing between microhabitats of sampled bryophyte assemblages when exploring the patterns and drivers of bryophyte diversity along elevational gradients.

Holographic approach for three-dimensional magnetotelluric modeling and CPU-GPU Parallel Architecture - De-Xiang Zhu; Shi-Kun Dai; Hong-Jun Tian; Qing-Rui Chen; Wen-Xue Zhao (Applied Geophysics, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Global trends in staphylococcus aureus-related lower respiratory infections from 1990 to 2021: findings from the 2021 global burden of disease report - Hong Chen; Shuang Song; Rui Cui; Yong-Wang Feng; Peng Ge (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Ginsenoside Rf in wild ginseng adventitious roots extract inhibits melanogenesis via cAMP/PKA and NO/cGMP signalling pathways in α-melanocyte-stimulating hormone-stimulated B16F10 mouse melanoma cells and zebrafish - Hong Chen; Mengqiong Jian; Huanhuan Teng; Zhenzhuo Li; Xiaohao Xu; Xiangzhu Li; Rui Jiang; Daqing Zhao; Liwei Sun; Jianzeng Liu (Natural Product Research, 2025)

The curvilinear relationship between perceived stress and spicy food craving in Young females: A non-linear mediation effect of positive emotional experience of spicy food consumption - Huizhen Qiu; Yidan Rui; Yuchen Zhang; Meiqi Hu; Shuang Zheng; Nanlin Xu; Jiaqi Jing; Pengfei Han; Hong Chen; Xiao Gao (Food Quality and Preference, 2025)

Silver carp by-product hydrolysate: A promising mucin substitute for stimulating Akkermansia muciniphila growth and metabolic activity - Huijuan Zhang; Rui Zhang; Shengjun Chen; Ruifang Feng; Sam K.C. Chang; Yongkang Luo; Hui Hong; Yuqing Tan (Food Bioscience, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Axial chain rockbursts in deep tunnels excavated via drilling and blasting - Hong-Pu Li; Ben-Guo He; Xiang-Rui Meng; Shengcun Yan; Tao Chen (Tunnelling and Underground Space Technology, 2025)

Regulation pattern of carotenoid biosynthesis induced by low light stress in Dunaliella - Hao-Hong Chen; Jing-Xuan Wu; Rui-qi Chen; Sacha Fouquay O’Donnell; Ming-Hua Liang; Jian-Guo Jiang (Bioresource Technology, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Suitability and Bearing Behavior of PHC Pipe Piles in Underlying Mudstone - Qing-rui Feng; Hao-feng Xing; Hong-bo Chen; Hua Wei (Geotechnical and Geological Engineering, 2025)

Pre-industrial Common Era temperature fluctuations in South China inferred based upon bacterial tetraether lipids from Lake Poyang - Rui Miao; Hong Yang; Qin Leng; Yuwei Chen; Shangbin Xiao; Xiaoke Qiang; Xiangzhong Li; Yuan Yao; Zenghao Zhao; Hongxuan Lu; Zhonghui Liu; Huanye Wang; et al. (Quaternary Science Reviews, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Deformation mechanism and treatment technology research of coal pillars in acute inclined goafs under expressway - Wei-Xing Bao; Zhi-Wei Ma; Hong-Peng Lai; Rui Chen (Applied Geophysics, 2025)

Evaluating soil water and nitrogen transport, nitrate leaching and soil nitrogen concentration uniformity under sprinkler irrigation and fertigation using numerical simulation - Rui Chen; Xiaofang Chen; Hong Li; Jian Wang; Xin Guo (Journal of Hydrology, 2025)

The characteristics of phthalate acid esters and bisphenol A in PM2.5 of a petrochemical city: Concentrations, compositions, and health risk assessment in Dongying - Fangyun Long; Yanqin Ren; Yuanyuan Ji; Xurong Bai; Hong Li; Gehui Wang; Xiaoyu Yan; Yubao Chen; Junling Li; Haijie Zhang; Rui Gao; Fang Bi; et al. (Environmental Pollution, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Microwave replacing traditional concentrating process to promote the synthesis of mumefural in Prunus mume extract - Teng Long Miao; Shan Qin; Xiao Hong Chen; Long Yun Chen; Yan Qing Han; Yan Li Yuan; Xin Rui; Wei Li; Qiu Qin Zhang (Food Research International, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Effects of chitosan/eugenol-loaded IRMOF-3 nanoparticles composite films on reactive oxygen species metabolism and microbial community dynamics in postharvest strawberries - Yuyue Qin; Hongda Yu; Kejun Chen; Rui Cui; Jianxin Cao; Zhengxuan Wang; Zhi-Hong Zhang; Thanapop Soteyome (Food Bioscience, 2025)

Zein film loaded with Fructus Ligustri Lucidi essential oil: Preparation, characterization and application in fresh-cut apple preservation - Hong Chen; Chengyan Yang; Xiangxun Zhuansun; Yao Li; Rui Han; Longgang Wang; Shengqing Ding; Qi Liu (Food Control, 2025)

Poly-γ-glutamic acid chelates chromium (III) and copper (II), alleviating their toxicity in cucumber and affecting rhizosphere bacterial community assembly - Chaoyang Chen; Wenhui Yan; Yu Chen; Sijie Liu; Chuanjiang Nong; Liang Sun; Rui Wang; Hong Xu; Peng Lei; Yian Gu (Environmental Pollution, 2025)

ε-Poly-L-lysine/rhamnolipid bifunctional coating based on green electrostatic assembly technology for fruit packaging and preservation - Quanfei Li; Qian Chen; Kai Yang; Hao Liu; Delei Xu; Yian Gu; Liang Sun; Peng Lei; Rui Wang; Hong Xu (Chemical Engineering Journal, 2025)

Efficient resource recovery from food waste digestate via hydrothermal treatment and its application as organic fertilizer - Hong Chen; Jun Sheng; Qinhui Ye; Jun Li; Xin Yu; Hanyue Wu; Rui Zhang; Shiyi Zhao; Xiaoming Zou; Xiang Li; Gang Xue; Baoling Yuan (Bioresource Technology, 2025)

Development of a Novel TBM Tunnelling Test Platform and Its Application in Rock–Machine Interaction Analysis - Wei-Qiang Xie; Xiao-Li Liu; Rui-Peng Qian; Jian Chen; En-Zhi Wang; Wei Hong (Rock Mechanics and Rock Engineering, 2025)

A rapid increase of groundwater in 2021 over the North China Plain from GPS and GRACE observations - Rui Zhang; Yujie Peng; Nengfang Chao; Qi Ou; Gang Chen; Zhengtao Wang; Hong Zhu; Bing Liu; Zixin Zhang (GPS Solutions, 2025)

Travel time calculation of seismic waves on complex surfaces using the group marching method - Ping Zhang; Fan-chang Meng; Xiao-hang Zhao; Jian-hui Deng; Rui Chen; Hong-yong Ren; Xiang-yu Tan; Gong-min Chen (Applied Geophysics, 2024)

Evaluation of water distribution and uniformity of sprinkler irrigation based on harmonic analysis and finite element method - Xiaofang Chen; Rui Chen; Jian Wang; Hong Li; Weibin Zhang (Biosystems Engineering, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Protective mechanism of antioxidant peptides derived from dry-cured ham against ultraviolet A-induced oxidative damage in HaCat cells - Rui-hong Xie; Shan Xiao; Da Ma; Bo Wang; Guan-chao Chen; Jun-han Xiang; Ji-hui Wang (Food Bioscience, 2024)

Screening and tentatively identifying of volatile hazards of desiccant and deoxidizer in food package - Hongyi Liu; Rui Fan; Siting Li; Hong Zhang; Zhou Chen; Aijin Ma; Yingmin Jia (Food Control, 2024)

The fate of organic compounds in organic waste during torrefaction and implications for its valorization - Yi Hu; Rui Yang; Yiping Wu; Xuejiao Chen; Wei Lin; Hong Wang; Zhiyong Qi; Dongdong Zhang; Lin Ouyang (Environmental Pollution, 2024)

Assessment of brittle failure in deep tunnels via true triaxial compression - Ben-Guo He; Hong-Pu Li; Xiang-Rui Meng; Si-Yuan Dou; Shengcun Yan; Tao Chen (Tunnelling and Underground Space Technology, 2024)

Nano Fe3O4 improved the electron donating capacity of dissolved organic matter during sludge composting - Liu Chen; Zeyu Zhang; Rui Yang; Xiaojie Wang; Jieyu Yu; Hong Jiang; Wenjie Zhang; Beidou Xi; Xiaojie Sun; Ningjie Li (Journal of Environmental Management, 2024)

Tetracycline adsorption on sludge-bamboo biochar prepared by gradient modification and co-pyrolysis: Performance evaluation and mechanism insight - Lijia Chen; Haiqing Yang; Ran Hong; Xuehui Xie; Rui Zuo; Xiaoying Zhang; Saisai Chen; Dayong Xu; Qingyun Zhang (Journal of Environmental Chemical Engineering, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Robust control algorithm designed for robotic legs of lunar-based equipment: Modeling and experiment - Zheng-Han Chen; Zhao-Dong Xu; Rui-Heng Wang; Hong-Fang Lu; Deng-Yun Yu; Jian-Zhong Yang; Xue-Liang Zhao; Zhong-Wei Hu; Sheng-Chao Zhen (Advances in Space Research, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Short-term exposure to ambient fine particulate matter constituents and myocardial infarction mortality - Yingxin Li; Bing Lu; Jing Wei; Qingqing Wang; Wancheng Ma; Rui Wang; Ruijun Xu; Zihua Zhong; Lu Luo; Xi Chen; Ziquan Lv; Suli Huang; et al. (Chemosphere, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Highly oxidized guaiane 12(8),15(6)-dilactones with neuroprotective activities from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Si-Qing Lou; Hong-Yu Chen; Di Luo; Lu Guo; Ning-Yu Chen; Rui Wu; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Separation, enrichment and cytoprotection of antioxidant peptides from Xuanwei ham using aqueous two-phase extraction - Rui-hong Xie; Shan Xiao; Xuan Chen; Bo Wang; Yao-yao Hu; Ji-hui Wang (Food Chemistry, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

Fe-Zn bimetallic oxide functionalized biochar for enhanced adsorption of enrofloxacin in water - Guodong Hong; Rui Shan; Jing Gu; Taoli Huhe; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

A polypyrrole-dopamine/poly(vinyl alcohol) anisotropic hydrogel for strain sensor and bioelectrodes - Shuang Chen; Bingyan Guo; Jiajun Yu; Zhuojun Yan; Rui Liu; Chaojie Yu; Zhongming Zhao; Hong Zhang; Fanglian Yao; Junjie Li (Chemical Engineering Journal, 2024)

Critical fractions in reclaimed water responsible for membrane fouling: Isolation, fouling characteristics, quantitative and qualitative variations in practical application - Yuan Bai; Rui-Ning Wang; Yin-Hu Wu; Song Xue; Zhuo Chen; Hong-Ying Hu (Science of The Total Environment, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Occurrence, physicochemical properties and environmental behavior of polychlorinated dibenzothiophenes: A comprehensive review and future perspectives - Chunmeng Ye; Yong Tu; Hong Ling; Yong Chen; Yang Liu; Rui Zhang; Xuesheng Zhang (Environmental Research, 2024)

Modeling of forced-vibration systems using continuous-time state-space neural network - Hong-Wei Li; Yi-Qing Ni; You-Wu Wang; Zheng-Wei Chen; En-Ze Rui; Zhao-Dong Xu (Engineering Structures, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Comparison of the ozone formation mechanisms and VOCs apportionment in different ozone pollution episodes in urban Beijing in 2019 and 2020: Insights for ozone pollution control strategies - Yunfeng Li; Zhenhai Wu; Yuanyuan Ji; Tianshu Chen; Hong Li; Rui Gao; Likun Xue; Yafei Wang; Yuxi Zhao; Xin Yang (Science of The Total Environment, 2024)

Metabolome analysis to investigate the effect of heavy metal exposure and chemoprevention agents on toxic injury caused by a multi-heavy metal mixture in rats - Jinyue Zhou; Hang Hong; Jinshun Zhao; Rui Fang; Shushu Chen; Chunlan Tang (Science of The Total Environment, 2024)

Evaluation on 131I production based on molten salt reactor off-gas extraction - Liang Chen; Liao-Yuan He; Bo Zhou; Gui-Feng Zhu; Yu-Han Fan; Hong-Jie Xu; Rui Yan; Yang Zou (Annals of Nuclear Energy, 2024)

Using 2DVD technology to explore droplet characteristic variations of sprinkler irrigation as affected by a maize canopy - Jian Wang; Yu Xiang; Rui Chen; Hong Li (Computers and Electronics in Agriculture, 2023)

Genomic and biogenic amine-reducing characterization of Lactiplantibacillus planatraum JB1 isolated from fermented dry sausage - Shan Qin; Xian Ming Zeng; Mei Jiang; Xin Rui; Wei Li; Ming Sheng Dong; Xiao Hong Chen; Qiu Qin Zhang (Food Control, 2023)

Pyroptosis induction synergized with IDO inhibition of ternary biomedicine for photodynamic activated tumor immunotherapy - Ali Chen; Ni Yang; Wei Zhang; Rongrong Zheng; Rui Yu; Renjing Kong; Yuqing Wang; Hong Cheng; Xiyong Yu; Shiying Li (Chemical Engineering Journal, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Phosphoproteomic Analysis Reveals the Predominating Cellular Processes and the Involved Key Phosphoproteins Essential for the Proliferation of Toxoplasma gondii - Xin-zhu Chen; Rui-xue Bai; Fei-yu Qin; Hong-juan Peng; Jin-feng Ren; Lang Hu; Yu-di Li; Cheng He (Acta Parasitologica, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Evaluating soil water movement and soil water content uniformity under sprinkler irrigation with different soil texture and irrigation uniformity using numerical simulation - Rui Chen; Hong Li; Jian Wang; Xin Guo; Yu Xiang (Journal of Hydrology, 2023)

Investigation of Campbell mode with automatic calibration operated in fission chamber-based neutron flux monitoring system on EAST - Li Yang; Li-Qun Hu; Guo-Qiang Zhong; Hong-Rui Cao; Jin-Long Zhao; Yong-Qiang Zhang; Wei-Kun Chen (Annals of Nuclear Energy, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Characterization of a gE/gI/TK gene-deleted pseudorabies virus variant expressing the Cap protein of porcine circovirus type 2d - Rui-Qin Xu; Lin-Qing Wang; Hui-Hua Zheng; Run-Bo Tian; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Effects of Fe and cost-effective media composition on arsenopyrite bioleaching by Sulfobacillus thermosulfidooxidans - Hong-Rui Chen; Duo-Rui Zhang; Xiao-Juan Zhao; Qian Li; Yu-Ting Liang; Eva Pakostova; Yan Zhang; Yong-Bin Yang (Chemical Engineering Journal, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Rare loss-of-function variants reveal threshold and multifactorial inheritance of dextrocardia - Zhongzhong Chen; Yunqian Gao; Lei Lu; Nan Li; Pei Liu; Rui Peng; Lingling Liu; Hefeng Huang; Qihua Fu; Haifa Hong; Jianguo Zhang; Hongyan Wang (Science Bulletin, 2023)

Elevation, bedrock exposure, land use, interbedded limestone and clastic rock, and vegetation coverage dominate the spatiotemporal variability of soil erosion in karst basin - Mei Chen; Jia-yong Gao; Hong-lian Chen; Jun Jing; Rui Li (Journal of Mountain Science, 2023)

Influence of calcination temperature on the evolution of α-MoO3 nanosheets catalyst for aqueous phase reforming of biogas slurry - Jian Wang; Yuxuan Chen; Weigao Zhao; Rui Liang; Beibei Yan; Junyu Tao; Hong Su; Guanyi Chen (Fuel, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

One-dimensional self-weight consolidation of layered soil under variable load and semi-permeable boundary condition - Hong-Xin Chen; Shi-Jin Feng; Zhang-Wen Zhu; Liang Gao; Zhang-Long Chen; Shu-Rui Wang (Computers and Geotechnics, 2023)

Structural characterization of a pectic polysaccharide from laoshan green tea and its inhibitory effects on the production of NO, TNF- α and IL-6 - Fan Liu; Rongshen Wang; Ying Chen; Rui Geng; Hong Gao; Feng Wang; Xiaoxiao Liu; Wanzhong Li (Natural Product Research, 2023)

Gold endowment and unloading along pathway for giant gold mineralization: Insights from spatiotemporal variations of in-situ pyrite geochemistry and gold fineness from the Jiaodong gold deposits, north China Craton - Ting-Guang Lan; Hong Wang; Hong-Rui Fan; Thomas Ulrich; Huan-Long Hu; You-Wei Chen; Lei Shu (Gondwana Research, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Novel adsorbent synthesized from red mud and acid mine drainage for enhanced contaminant removal: Industrial waste transformation, adsorbent performance and metal(loid) removal mechanisms - Duo-Rui Zhang; Hong-Rui Chen; Jin-Lan Xia; Zhen-Yuan Nie; Xiao-Juan Zhao; Eva Pakostova (Chemical Engineering Journal, 2023)

Physicochemical Characterization of Three Active Pharmaceutical Ingredients for Compound Glycyrrhizin Solid Formulation and Compatibility Analysis via Thermal and Non-thermal Techniques - Xiang-yun Xie; Zhan-ying Chang; Chun-li Chen; Liang Zhang; Mei Wang; Cheng Tang; Hong-rui Xue; Xiao-li Gao (Journal of Pharmaceutical Innovation, 2023)

Internet addiction-induced brain structure and function alterations: a systematic review and meta-analysis of voxel-based morphometry and resting-state functional connectivity studies - Jing-Ting Sun; Bo Hu; Tian-Qi Chen; Zhu-Hong Chen; Yu-Xuan Shang; Yu-Ting Li; Rui Wang; Wen Wang (Brain Imaging and Behavior, 2023)

The distribution and emission of CO2, CH4 and light hydrocarbons in an anticyclonic eddy of the Kuroshio extension - Xiao-Jun Li; Jian Wang; Hao Qiao; Rui-Chen Zhu; Hong-Hai Zhang; Zhao-Hui Chen; Andrew Montgomery; Shan Zheng; Guang-Chao Zhuang (Frontiers in Marine Science, 2023)
Mesoscale eddies are energetic and swirling circulations that frequently occur in the open ocean. The effects of mesoscale eddies on the biogeochemical cycling of climate-relevant gases remain poorly constrained. We investigated the distribution and air-sea fluxes of CO 2 , methane, and five non–methane hydrocarbons (NMHCs) in an anticyclone eddy of Kuroshio Extension during September 2019. Within eddy core, intense stratification hindered the replenishment of nutrients and favored the growth of small-size phytoplankton, such as Prochlorococcus . Seawater pCO 2 decreased from 406.1 μatm at the eddy outside to 377.5 μatm at the eddy core, accompanied by a decrease in surface seawater temperature from 26.7 °C to 25.2 °C. The vertical distribution of methane (0.3-9.9 nmol L -1 ) was influenced by the eddy process, with a maximum at 80 m in the eddy core, which might be attributed to the degradation of phosphonates sustained by Prochlorococcus . The concentrations of five NMHCs (ethane, ethylene, propane, propylene, and isoprene) ranged from 17.2-126.2, 36.7-168.1, 7.5-29.2, 22.6-64.1, 54.5-172.1, 3.5-27.9 pmol L -1 , respectively. Isoprene correlated well with Chl- a concentrations at the eddy core, while no significant correlation was observed at the eddy outside. Air-sea fluxes of CO 2 and isoprene associated with the eddy core were higher than those of the eddy outside, while the maximum ventilation of methane and other NMHCs (ethane, ethylene, propane, and propylene) was found at the eddy outside. Collectively, physical processes such as eddies impact the production and distribution of light hydrocarbons in seawater and further influence their regional emissions to the atmosphere.

Distress mechanism and treatment measures in construction of large cross-section tunnel passing through Q2 soft-plastic loess layer - Qiuyang Hong; Hongpeng Lai; Yuyang Liu; Rui Chen (Bulletin of Engineering Geology and the Environment, 2023)

Assessing the effects of short-term traffic restriction policies on traffic-related air pollutants - Xiao-Rui Fang; Xing-Hang Zhu; Xing-Zhou Li; Zhong-Ren Peng; Hu Qingyao; Hong-Di He; AJ Yuan Chen; Huang Cheng (Science of The Total Environment, 2023)

Multi-model analysis of historical runoff changes in the Lancang-Mekong River Basin – Characteristics and uncertainties - Yuxin Li; Aifang Chen; Ganquan Mao; Penghan Chen; Hao Huang; Hong Yang; Zifeng Wang; Kai Wang; He Chen; Ying Meng; Rui Zhong; Pengfei Wang; et al. (Journal of Hydrology, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

Two-step sequential bio-oxidation of arsenopyrite catalyzed by a mesophilic bacterium eliminates hazardous Fe(III)/As-bearing products and enhances mineral dissolution - Hong-Rui Chen; Qian Li; Xiao-Juan Zhao; Duo-Rui Zhang; Eva Pakostova (Chemical Engineering Journal, 2023)

Highly stability Cu+ species in hollow Cu2O nanoreactors by modulating cavity size for CO2 electroreduction to C2+ products - Rui Zhang; Feifei Chen; Haokun Jin; Yong Zhang; Xiaoya Hao; Yingda Liu; Tianming Feng; Xinghua Zhang; Zunming Lu; Weihua Wang; Feng Lu; Hong Dong; et al. (Chemical Engineering Journal, 2023)

A model description of beta oscillations in the external globus pallidus - Mingming Chen; Yajie Zhu; Rui Zhang; Renping Yu; Yuxia Hu; Hong Wan; Dezhong Yao; Daqing Guo (Cognitive Neurodynamics, 2023)

Quality prediction of tractor rotary tillage based on BiConvLSTM with self-attention - Ruo-chen Li; Chang-kai Wen; Shu-yan Li; Rui Li; Hong-yu Pu; Yu Jiang; Zheng-he Song (Computers and Electronics in Agriculture, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

Kidney Mesenchymal stem cells alleviate cisplatin-induced kidney injury and apoptosis in rats - Rui-ning Liang; De-qi Yan; Xing-ping Zhang; Xu Chen; Wen-hui Zhang; Hong-lin Jia (Tissue and Cell, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Bioactive icetexane and abietane diterpenes from Isodon phyllopodus - Rui Deng; Juan Zou; Chen-Liang Zhao; Ye-Meng Yang; Chuen Fai Ku; Yu Zhu; Zheng-Ming Liang; Jiang-Hai Ye; Lu-Tai Pan; Hong-Jie Zhang (Natural Product Research, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Study on the prepared bio-oil by catalytic hydrothermal liquefaction of antibiotic residues in ethanol-water reaction system with transition metal modified HZSM-5 - Jian Yang; Rui Ma; Yi Xing; Hongzhi Ma; Biqin Dong; Hongxia Li; Chen Hong; Changlei Xia (Fuel, 2023)

Combination of pulsed electric field and pH shifting improves the solubility, emulsifying, foaming of commercial soy protein isolate - Rui Wang; Lang-Hong Wang; Qing-Hui Wen; Fei He; Fei-Yue Xu; Bo-Ru Chen; Xin-An Zeng (Food Hydrocolloids, 2023)

Formation mechanism and metabolic pathways of photogranule in batch and continuous-flow mode under high salinity stress - Jing Zhu; Hong You; Zhipeng Li; Binghan Xie; Weirun Li; Shaojie Qi; Rui Wang; Hongying Chen; Binyu Ma; Yi Ding; Haili Tan; Feng Liu; et al. (Chemical Engineering Journal, 2023)

Lanthanoid hydrogen-bonded organic frameworks: Enhancement of luminescence by the coordination-promoted antenna effect and applications in heavy-metal ion sensing and sterilization - Yun-Lan Li; Hai-Ling Wang; Zhi-Chuan Chen; Zhong-Hong Zhu; Yan-Cheng Liu; Rui-Yun Yang; Fu-Pei Liang; Hua-Hong Zou (Chemical Engineering Journal, 2023)

Plant-associated Microbe System in Treatment of Heavy Metals–contaminated Soil: Mechanisms and Applications - Zhiming Ren; Rui Cheng; Peng Chen; Yuanyuan Xue; Hong Xu; Yao Yin; Guangtuan Huang; Wei Zhang; Lehua Zhang (Water, Air, & Soil Pollution, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

Optimizing staggered-grid finite-difference method based on the least-squares combination of the square window function - Chao-pu Chen; Hong Liu; Zhi-yang Wang; Wen-lei Bai; Cheng-fang Zhang; Zi-rui Meng (Applied Geophysics, 2021)

Discovery of novel DGAT1 inhibitors by combination of machine learning methods, pharmacophore model and 3D-QSAR model - Hui Zhang; Chen Shen; Hong-Rui Zhang; Wen-Xuan Chen; Qing-Qing Luo; Lan Ding (Molecular Diversity, 2021)

The correlation of altitude with gingival status among adolescents in western China: a cross-sectional study - Zhiwu Wu; Rui Zhang; Li Cheng; Ruilie Cai; Hong Chen; Ran Cheng; Tao Hu (Environmental Geochemistry and Health, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Arbuscular mycorrhizal colonization rate of an exotic plant, Galinsoga quadriradiata, in mountain ranges changes with altitude - Gang Liu; Rui-Ling Liu; Wen-Gang Zhang; Ying-Bo Yang; Xiao-Qiong Bi; Ming-Zhu Li; Xiao-Yan Chen; Hua Nie; Zhi-Hong Zhu (Mycorrhiza, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Isolation and molecular characterization of bovine herpesvirus 4 from cattle in mainland China - Jun Lin; Rui-Hong Chen; Mu-Jiao Yang; Yuan-Mao Zhu; Fei Xue (Archives of Virology, 2021)

A case study on deformation characteristics of a large cross-section tunnel passing through a soft-plastic layer with different spatial locations - Qiuyang Hong; Hongpeng Lai; Yuyang Liu; Rui Chen; Cheng Liu; Juntai Xie (Arabian Journal of Geosciences, 2021)

Study on NOx removal from simulated flue gas by an electrobiofilm reactor: EDTA-ferrous regeneration and biological kinetics mechanism - Nan Liu; Ying-ying Li; Du-juan Ouyang; Rui Guo; Run Chen; Wei Li; Ji-xiang Li; Ji-hong Zhao (Environmental Science and Pollution Research, 2021)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Comparative study on the bioaccumulation of lead, cadmium and nickel and their toxic effects on the growth and enzyme defence strategies of a heavy metal accumulator, Hydrilla verticillata (L.f.) Royle - Hong Zhang; Ling-Lei Zhang; Jia Li; Min Chen; Rui-Dong An (Environmental Science and Pollution Research, 2020)

Differential anthocyanin accumulation in radish taproot: importance of RsMYB1 gene structure - Biao Lai; Yuanyi Cheng; Hong Liu; Qiuxia Wang; Qi Wang; Chunlan Wang; Rui Su; Fabo Chen; Huicong Wang; Lina Du (Plant Cell Reports, 2020)

Visualization and analysis of mapping knowledge domain of oxidation studies of sulfide ores - Rui Hong; Hui Liu; Chenglang Xiang; Yimeng Song; Chen Lv (Environmental Science and Pollution Research, 2020)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Development of a colloidal gold-based immunochromatographic strip for rapid detection of Rice stripe virus - De-qing Huang; Rui Chen; Ya-qin Wang; Jian Hong; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2019)

Complete mitochondrial genome of a kind of snakehead fish Channa siamensis and its phylogenetic consideration - Rui Li; Gang Wang; Zheng-Yong Wen; Yuan-Chao Zou; Chuan-Jie Qin; Yu Luo; Jun Wang; Gui-Hong Chen (Genes & Genomics, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Estimating cadmium concentration in the edible part of Capsicum annuum using hyperspectral models - Ting Wang; Hong Wei; Cui Zhou; Yanwen Gu; Rui Li; Hongchun Chen; Wenchao Ma (Environmental Monitoring and Assessment, 2017)

Evaluation of bioaugmentation and biostimulation on arsenic remediation in soil through biovolatilization - Peng Chen; Jin Li; Hong-Yan Wang; Rui-Lun Zheng; Guo-Xin Sun (Environmental Science and Pollution Research, 2017)

mtDNA Heteroplasmy in Monozygotic Twins Discordant for Schizophrenia - Hong Li; Rui Bi; Yu Fan; Yong Wu; Yanqing Tang; Zongchang Li; Ying He; Jun Zhou; Jinsong Tang; Xiaogang Chen; Yong-Gang Yao (Molecular Neurobiology, 2017)

Occurrence and profiles of polybrominated diphenyl ethers (PBDEs) in riverine sediments of Shanghai: a combinative study with human serum from the locals - Ming-Hong Wu; Ben-Tuo Xu; Gang Xu; Ming-Nan Wang; Jing Ma; Chen-Yuan Pan; Rui Sun; Tao Han; Liang Tang (Environmental Geochemistry and Health, 2017)

Synthesis and evaluation of multifunctional ferulic and caffeic acid dimers for Alzheimer’s disease - Xi-xin He; Xiao-hong Yang; Rui-ying Ou; Ying Ouyang; Sheng-nan Wang; Zi-wei Chen; Shi-jun Wen; Rong-biao Pi (Natural Product Research, 2017)

Neuroprotective Effects of a PSD-95 Inhibitor in Neonatal Hypoxic-Ischemic Brain Injury - Baofeng Xu; Ai-Jiao Xiao; Wenliang Chen; Ekaterina Turlova; Rui Liu; Andrew Barszczyk; Christopher L. F. Sun; Ling Liu; Michael Tymianski; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

Efficacy of Bt maize producing the Cry1Ac protein against two important pests of corn in China - Hong-Xing Chen; Rui Yang; Wang Yang; Liu Zhang; Ibrahima Camara; Xue-Hui Dong; Yi -Qing Liu; Wang-Peng Shi (Environmental Science and Pollution Research, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Progression and inflammation of human myeloid leukemia induced by ambient PM2.5 exposure - Xiao-Ting Jin; Mei-Lan Chen; Rui-Jin Li; Quan An; Li Song; Yi Zhao; Hong Xiao; Long Cheng; Zhuo-Yu Li (Archives of Toxicology, 2016)

Magnetic effervescent tablet-assisted ionic liquid dispersive liquid–liquid microextraction of selenium for speciation in foods and beverages - Xiaojun Wang; Long Wu; Jiaqi Cao; Xincheng Hong; Rui Ye; Weiji Chen; Ting Yuan (Food Additives & Contaminants: Part A, 2016)

Emergence of reticuloendotheliosis virus in pigeons in Guangdong Province, Southern China - Shao-Lun Zhai; Sheng-Nan Chen; Tao Lin; Xiao-Hui Wen; Wen-Kang Wei; Dian-Hong Lv; Rui-Ai Chen (Archives of Virology, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Lysobacter chengduensis sp. nov. Isolated from the Air of Captive Ailuropoda melanoleuca Enclosures in Chengdu, China - Caifang Wen; Lixin Xi; Rong She; Shan Zhao; Zhongxiang Hao; Lu Luo; Hong Liao; Zhenrong Chen; Guoquan Han; Sanjie Cao; Rui Wu; Qigui Yan; et al. (Current Microbiology, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

Pectin Modifications: A Review - Jun Chen; Wei Liu; Cheng-Mei Liu; Ti Li; Rui-Hong Liang; Shun-Jing Luo (Critical Reviews in Food Science and Nutrition, 2015)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Retraction Note to: Meta-analysis of the relationship between single nucleotide polymorphism rs72689236 of caspase-3 and Kawasaki disease - Yanlin Xing; Hong Wang; Xiaomei Liu; Xianyi Yu; Rui Chen; Ce Wang; Xuexin Yu; Le Sun (Molecular Biology Reports, 2015)

Characterization of 15 polymorphic microsatellite loci for the jellyfish Rhopilema esculentum - Ling Zhu; Ao-ao Yang; Chun-ya Zhou; Hong Yang; Xiao-rui Luo; Si-Qing Chen; Zhi-meng Zhuang (Conservation Genetics Resources, 2015)

Long-Term Effectiveness of Total Hip Replacement with the Collum Femoris Preserving Prosthesis - Rui-jin You; Wen-zhong Zheng; Kun Chen; Hong-sheng Lv; Dian-feng Huang; Yi-zeng Xiao; De-yu Yang; Zhai-quan Su (Cell Biochemistry and Biophysics, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

RETRACTED ARTICLE: Meta-analysis of the relationship between single nucleotide polymorphism rs72689236 of caspase-3 and Kawasaki disease - Yanlin Xing; Hong Wang; Xiaomei Liu; Xianyi Yu; Rui Chen; Ce Wang; Xuexin Yu; Le Sun (Molecular Biology Reports, 2014)

Gabapentin Enhances the Morphine Anti-Nociceptive Effect in Neuropathic Pain via the Interleukin-10-Heme Oxygenase-1 Signalling Pathway in Rats - Yu-Hua Bao; Quan-Hong Zhou; Rui Chen; Hao Xu; Lu-Lu Zeng; Xin Zhang; Wei Jiang; Dong-Ping Du (Journal of Molecular Neuroscience, 2014)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

Shoot regeneration and cryopreservation of shoot tips of apple (Malus) by encapsulation–dehydration - Bai-Quan Li; Chao-Hong Feng; Ling-Yun Hu; Min-Rui Wang; Long Chen; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Time-dependent damage constitutive model for the marble in the Jinping II hydropower station in China - Bing-Rui Chen; Xiao-Jun Zhao; Xia-Ting Feng; Hong-Bo Zhao; Shan-Yong Wang (Bulletin of Engineering Geology and the Environment, 2014)

Construction, characterization and expression of full length cDNA clone of sheep YAP1 gene - Wei Sun; Da Li; Rui Su; Hassan H. Musa; Ling Chen; Hong Zhou (Molecular Biology Reports, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Y chromosome diversity and paternal origin of Chinese cattle - Ran Li; Wen-Mei Xie; Zhen-Hua Chang; Shao-Qiang Wang; Rui-Hua Dang; Xian-Yong Lan; Hong Chen; Chu-Zhao Lei (Molecular Biology Reports, 2013)

Microbial Treatment for Prevention and Removal of Paraffin Deposition on the Walls of Crude Pipelines - Jiang Hong Liu; Yun Peng Jia; Yi Tong Chen; Rui Dan Xu (Indian Journal of Microbiology, 2013)

Effect of Intravenous Infusion of Dexmedetomidine Combined with Inhalation of Isoflurane on Arterial Oxygenation and Intrapulmonary Shunt During Single-Lung Ventilation - Rui Xia; Hong Yin; Zhong-yuan Xia; Qing-jun Mao; Gong-da Chen; Wei Xu (Cell Biochemistry and Biophysics, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

How immunogenetically different are domestic pigs from wild boars: a perspective from single-nucleotide polymorphisms of 19 immunity-related candidate genes - Shanyuan Chen; Rui Gomes; Vânia Costa; Pedro Santos; Rui Charneca; Ya-ping Zhang; Xue-hong Liu; Shao-qing Wang; Pedro Bento; Jose-Luis Nunes; József Buzgó; Gyula Varga; et al. (Immunogenetics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

A stabilized least-squares imaging condition with structure constraints - Guo-Chang Liu; Xiao-Hong Chen; Jian-Yong Song; Zhen-Hua Rui (Applied Geophysics, 2012)

Pollen development of Cardiocrinum giganteum (Wall.) Makina in China - Hong-Na Chen; Chun-Hai Zhao; Xiao-Rui Liu; Jia-Xi Liu (Plant Systematics and Evolution, 2012)

Mantle-derived noble gases in ore-forming fluids of the granite-related Yaogangxian tungsten deposit, Southeastern China - Rui-Zhong Hu; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Jian-Tang Peng; You-Qiang Qi; Li-Yan Wu; Wen-Feng Wei (Mineralium Deposita, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

A New bis(rhodamine)-Based Fluorescent Chemosensor for Fe3+ - Xiaopo Chen; Huijie Hong; Rui Han; Di Zhang; Yong Ye; Yu-fen Zhao (Journal of Fluorescence, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Enzymatic condensation of dopamine and acetaldehyde: a salsolinol synthase from rat brain - Xuechai Chen; Abida Arshad; Hong Qing; Rui Wang; Jianqing Lu; Yulin Deng (Biologia, 2011)

A systemic proteomic analysis of Populus chloroplast by using shotgun method - Hong-Mei Yuan; Kai-Long Li; Rui-Juan Ni; Wen-Dong Guo; Zhuo Shen; Chuan-Ping Yang; Bai-Chen Wang; Gui-Feng Liu; Chang-Hong Guo; Jing Jiang (Molecular Biology Reports, 2011)

Effects of Copper Exposure on Expression of Glutathione-Related Genes in Acidithiobacillus ferrooxidans - Jin-lan Xia; Shun Wu; Rui-yong Zhang; Cheng-gui Zhang; Huan He; Hong-chen Jiang; Zhen-yuan Nie; Guan-zhou Qiu (Current Microbiology, 2011)

Dynamics of vegetation and soil carbon and nitrogen accumulation over 26 years under controlled grazing in a desert shrubland - Zhi-Yu Zhou; Feng-Rui Li; Shan-Ke Chen; Hong-Rong Zhang; Guangdi Li (Plant and Soil, 2011)

He and Ar isotopic compositions and genetic implications for the giant Shizhuyuan W–Sn–Bi–Mo deposit, Hunan Province, South China - Li-Yan Wu; Rui-Zhong Hu; Jian-Tang Peng; Xian-Wu Bi; Guo-Hao Jiang; Hong-Wei Chen; Qiao-Yun Wang; Ya-Ying Liu (International Geology Review, 2011)

The Qiyugou gold-bearing breccia pipes, Xiong'ershan region, central China: fluid-inclusion and stable-isotope evidence for an origin from magmatic fluids - Hong-Rui Fan; Fang-Fang Hu; Simon A. Wilde; Kui-Feng Yang; Chen-Wei Jin (International Geology Review, 2011)

Inhibitor of DNA binding-1 promotes the migration and proliferation of endothelial progenitor cells in vitro - Hong Wang; Yang Yu; Rui-wei Guo; Yan-kun Shi; Ming-bao Song; Jian-fei Chen; Shi-yong Yu; Yang-guang Yin; Pan Gao; Lan Huang (Molecular and Cellular Biochemistry, 2010)

Protective effect of DNA-mediated immunization with liposome-encapsulated GRA4 against infection of Toxoplasma gondii - Rui Chen; Shao-hong Lu; Qun-bo Tong; Di Lou; Dong-yan Shi; Bing-bing Jia; Guo-ping Huang; Jin-fu Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Complete genomic sequence analyses of Turnip mosaic virus basal-BR isolates from China - Hong-Yan Wang; Jin-Liang Liu; Rui Gao; Jia Chen; Yun-Hua Shao; Xiang-Dong Li (Virus Genes, 2009)

Transcriptional suppression of IE180 and TK promoters by the EP0 of pseudorabies virus strains Ea and Fa - Hong Guo; Rui Zhou; Yang Xi; Shaobo Xiao; Huanchun Chen (Virus Genes, 2009)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)